Expression of human β-defensin 2 (hBD-2) inHelicobacter pylori induced gastritis: antibacterial effect of hBD-2 against Helicobacter pylori. (1st October 2001) - Hamanaka, Y; Nakashima, M; Wada, A; Ito, M; Kurazono, H; Hojo, H; Nakahara, Y; Kohno, S; Hirayama, T; Sekine, I
Abstract : BACKGROUND: Human β-defensin 2 (hBD-2) plays a role in the innate defence system at mucosal surfaces. Colonisation of Helicobacter pylori in the stomach is an important pathological factor in gastrointestinal illnesses, including gastritis, peptic ulcer, and gastric adenocarcinoma. AIMS: To evaluate the antibacterial role of hBD-2 against H pylori infection in the gastric mucosa. SUBJECTS: Biopsied gastric mucosa specimens from H pylori positive (n=6) and H pylori negative (n=6) individuals were used. H pylori was determined by the presence of urease activity and microscopic examination. METHODS: The specimens were examined for hBD-2 expression by reverse transcription-polymerase chain reaction (RT-PCR), immunohistochemistry, and in situ hybridisation. The antibacterial effect of hBD-2 against H pylori was evaluated by the number of colony forming units of H pylori after incubation with 0, 10 −9, 10 −8, 10 −7, 10 −6, or 10 −5 M of hBD-2 peptide. RESULTS: All six H pylori positive specimens expressed a high level of hBD-2 mRNA while hBD-2 mRNA was not detected in the H pylori negative specimens by RT-PCR. Immunohistochemistry using anti-hBD-2 antiserum revealed that hBD-2 was expressed in the surface epithelium of H pylori infected specimens. In gastric specimens obtained after H pylori eradication, hBD-2 immunoreactivity had dramatically decreased. In situ hybridisation confirmed that hBD-2 transcripts were localised in the epithelium of H pylori infected gastric specimens. Incubation with hBD-2 reduced the growth rate of cultured H pylori in a dose dependent manner, and incubation with 10 −5 M hBD-2 completely inhibited the proliferation of H pylori . CONCLUSIONS: H pylori infection induces hBD-2 expression in the human gastric epithelium. hBD-2 inhibited the growth of H pylori in vitro, suggesting that hBD-2 plays an antibacterial role in H pylori induced gastritis.